Effects of taurine combined with caffeine on repetitive sprint exercise performance and cognition in a hypoxic environment - Jie, Liu; Wenchao, Rong (Nature Research, 2025)
The impact of hypoxic repetitive sprint training on the overall performance of team sports remains controversial due to the specific nature of the exercise capacity required for team sports. While taurine and caffeine are widely utilized as supplements for repetitive sprint exercise in normoxic environments, their efficacy in hypoxic environments remains to be fully understood. Therefore, additional research is needed to explore the role of supplementation in hypoxic conditions. This study was to investigate the effects of caffeine (C), taurine (T), caffeine, and taurine co-ingestion (TC) or placebo (P) on repetitive sprint exercise performance and related physiological responses after exhaustion exercise in team athletes under simulated hypoxic conditions. A double-blind crossover randomized controlled experimental design was employed. 16 male participants (Age:23.69 ± 2.15 years, Body mass: 75.04 ± 7.79 kg, Height:1.78 ± 0.06 m) volunteered to receive four different supplement ingestions to complete the exercise tests: (1) placebo (5 mg/kg maltodextrin), (2) taurine (50 mg/kg), (3) caffeine (5 mg/kg), (4) taurine + caffeine (50 mg/kg + 5 mg/kg). All selected participants were university football players who had undergone rigorous training regimens (85–95% of maximum heart rate, duration of 60 min, with more than five training sessions per week). All participants completed an exhaustion test and subsequent repetitive sprint exercise in a simulated hypoxic environment (A simulation of a soccer game in sports mode). Time to exhaustion (TTE), peak power (PP), and mean power (MP) were recorded at the end of the exhaustion test and during the repetitive sprint exercise, respectively. This study designed an exercise protocol for repetitive sprinting after exhaustion exercise based on the pattern of play in football. The following variables were monitored throughout the experiments: heart rate (HR), blood lactate (B[La]), arterial oxygen saturation (SpO2), dyspnea, and rating of perceived exhaustion (RPE). The Stroop Test was administered at three separate time points: pre-test, mid-test, and post-test, throughout the exercise trial. The countermovement jump test (CMJ) was carried out at three specific time points: before the test, 3 min after the test, and 6 min after the test. The caffeine (C:618.56 + 42.50 s, p = 0.027, d = 0.996) and taurine + caffeine (TC: 613.69 + 37.74 s, p = 0.041, d = 0.902) groups significantly improved time to exhaustion compared to the placebo group. Blood lactate was significantly higher in the taurine + caffeine group than in the placebo group after repetitive sprint exercise (P: 9.87 ± 1.97, TC: 12.31 ± 2.54, p = 0.016). The caffeine group significantly reduced dyspnea, and rating of perceived exhaustion after repetitive sprint exercise (p < 0.05). The taurine (T: 43.42 ± 3.46, p = 0.005), caffeine (C: 44.11 ± 4.72, p < 0.001), and taurine + caffeine (TC: 43.04 ± 3.30, p = 0.011) groups all showed an increase in pre-exercise countermovement jump height. The caffeine group significantly reduced the consistent response time (p = 0.023) and inconsistent response time (p < 0.001) in the Stroop Test compared to the placebo group. Caffeine, along with combined taurine, significantly prolonged the duration of exhaustion exercise in a hypoxic environment; however, it did not affect subsequent repetitive sprint performance. Additionally, caffeine supplementation had a positive impact on cognitive performance during hypoxic training.